Determinants of Share Price of Dhaka Stock Exchange (American Journal of Applied Statistics and Economics, 2025)
This study investigates at the main factors influencing share prices on the Dhaka Stock Exchange (DSE), one of the two main stock exchanges in Bangladesh. Stock markets provide as venues for businesses to generate cash through the issuance of securities, which investors’ then trade. Primary measures of investor sentiment and stock prices are extremely volatile and impacted by a number of qualitative (goodwill, industry circumstances, and market hype) and quantitative (earnings per share, ROA, and net asset value) variables. The present research inspects 206 firms that are listed on the DSE and investigates the influence of distinct quantitative elements on share prices, including liquidity, EPS, ROA, NAV, business size, and cash dividend rate (CDR). The results indicate that these variables explain 56% of the volatility in share price. Notably, share prices are negatively impacted by ROA and liquidity, while CDR has the most favorable impact. Additionally, the analysis shows that there is considerable multi-co linearity among the variables, indicating that removing variables with higher p-values enhances the accuracy of the model. The outcomes of the research provide investors with insightful information that helps them make better decisions by demonstrating how important financial parameters impact share prices. Furthermore, the results lay the groundwork for future studies that examine other variables affecting DSE share price swings. The study emphasizes the difficulty of anticipating share prices because of both erratic market dynamics and controlled financial considerations.